Pembinaan Karakter Disiplin Dan Akhlak Karimah Santri Putra Melalui Budaya Pesantren Di Pondok Pesantren Hidayatul Mubtadiin Jati Agung Lampung - Yanwari, Yanwari; Pujianti, Etika; Widiastuti, Nur (EDU SOCIETY: JURNAL PENDIDIKAN, ILMU SOSIAL DAN PENGABDIAN KEPADA MASYARAKAT, 2025)
Abstract This study aims to analyze in depth how Islamic boarding school culture functions as a cultural mechanism in fostering the disciplined character and noble morals of male students at the Hidayatul Mubtadiin Islamic Boarding School in Jati Agung, Lampung. This study uses a qualitative approach with a case study design to understand in-depth the role of Islamic boarding school culture in fostering the disciplined character and noble morals of male students at the Hidayatul Mubtadiin Islamic Boarding School in Jati Agung, Lampung. The research subjects were selected purposively, including kiai (Islamic religious teachers), ustadz (Islamic teachers), administrators, and male students. Data were collected through participant observation, in-depth interviews, and documentation studies. Data analysis was conducted thematically through data reduction, presentation, and drawing conclusions, with data validity guaranteed through triangulation of sources and techniques. Based on the research results, Islamic boarding school culture at the Hidayatul Mubtadiin Islamic Boarding School in Jati Agung, Lampung functions effectively as a cultural mechanism in fostering the disciplined character and noble morals of male students. Character development is built through moral relationships between students and Islamic boarding school authority figures, fostering an internal sense of discipline. Habitual use of polite language and ethical communication plays a crucial role in fostering respect, humility, and ethical awareness among students. Furthermore, a culture of simplicity fosters self-control, gratitude, and moral maturity. These findings demonstrate that character development in Islamic boarding schools is integrated, sustainable, and based on the internalization of values.